The Analysis of Judicial Authority in Issuing Acquittal Decisions - shafa aistalia tsara dewi (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
The existence of courts aims to ensure fair and effective law enforcement. However, cases involving acquittals by the courts have caused controversy, especially when acquittals are deemed inconsistent with the public's sense of justice. This study analyzes the limits of the judge's authority in granting an acquittal. The research method in this study uses a normative juridical approach, focusing on analyzing the legal aspects that underlie the judge's decision. This study found that the importance of the integrity and morality of judges and the need to uphold the principles of justice in every decision taken. This study provides several suggestions, including the need to strengthen supervision of judges' authority and increase transparency in every court decision with clear and detailed explanations.